Dr. Edgar Vargas — Deep Plane Facelift — Nogales - Vargas, Edgar (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Edgar Vargas, practicing in Nogales, Mexico. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003377; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; mexico; nogales